2018
DOI: 10.1002/jper.18-0412
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid and salivary HIF‐1α, VEGF, and TNF‐α levels in periodontal health and disease

Abstract: Background: Hypoxia-inducible factor-1 alpha (HIF-1 ) is expressed as an adaptive response to hypoxia, mediates angiogenesis through the expression of vascular endothelial growth factor (VEGF) and can be induced by tumor necrosis factor-alpha (TNF-). This study aimed to investigate the gingival crevicular fluid (GCF) and salivary HIF-1 , VEGF, and TNF-levels in periodontal health and disease.Methods: A total of 87 individuals, 20 generalized aggressive periodontitis (G-AgP), 20 chronic periodontitis (CP), 26 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 50 publications
(116 reference statements)
5
59
0
Order By: Relevance
“…17 Increased HIF-1 protein expression levels have been shown in the gingival tissue of patients with periodontitis. 18,19 Recently, two clinical studies by Afacan et al 20 and Tayman et al 21 have reported that G-AgP and chronic periodontitis patients had significantly higher GCF HIF-1 levels than periodontally healthy controls. These findings suggest a possible association of HIF-1 with the pathophysiology of periodontal inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 Increased HIF-1 protein expression levels have been shown in the gingival tissue of patients with periodontitis. 18,19 Recently, two clinical studies by Afacan et al 20 and Tayman et al 21 have reported that G-AgP and chronic periodontitis patients had significantly higher GCF HIF-1 levels than periodontally healthy controls. These findings suggest a possible association of HIF-1 with the pathophysiology of periodontal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest a possible association of HIF-1 with the pathophysiology of periodontal inflammation. [18][19][20][21] As HIF-1 , under hypoxic condition, upregulates primer angiogenic mediator vascular endothelial growth factor (VEGF) 22,23 which is closely related to periodontal inflammation, wound healing and alveolar bone remodeling, [24][25][26] TNF-increases HIF-1 and its downstream effector VEGF in an oxygenindependent manner. 27,28 It has been reported that protein expressions and GCF total amounts of HIF-1 may be associated with VEGF and TNF-levels in patients with periodontitis, which in turn implies that TNF-/HIF-1 /VEGF pathway may involved in periodontal inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though a broad range of methods has been used to analyze protein signatures in saliva for the characterization of G‐AgP, spanning from immunoassays to mass spectrometric–based proteomics, [ 29‐31 ] most of them have by far failed to reach the clinical setting, due their laborious and complex configuration.…”
mentioning
confidence: 99%